Unicompartmental Knee Arthroplasty Has Lower Infection, Conversion, and Complication Rates Compared to High Tibial Osteotomy - Kahan, Michael E.; Chen, Zhongming; Angerett, Nathan R.; Sax, Oliver C.; Bains, Sandeep S.; Assayag, Michael J.; Delanois, Ronald E.; Nace, James (The Journal of Knee Surgery, 2022)
Introduction Isolated medial knee osteoarthritis can be surgically treated with either unicompartmental knee arthroplasty (UKA) or high tibial osteotomy (HTO). Proponents of UKA suggest superior survivorship, while HTO offers theoretically improved alignment and joint preservation delaying total knee arthroplasty (TKA). Therefore, we compared complications in a large population of patients undergoing UKAs or HTOs. We specifically assessed 90 days, 1 year, and 2 years: (1) periprosthetic joint infection (PJI) rates, (2) conversion to TKA rates, as well as (3) complication rates.Methods A review of an administrative claims database was used to identify patients undergoing primary UKA (n = 13,674) or HTO (n = 1,096) from January 1, 2010 to December 31, 2019. Complication rates at 90 days, 1 year, and 2 years were compared between groups using unadjusted odds ratios (ORs) with 95% confidence intervals. Subsequently, multivariate logistic regressions were performed for PJI and conversion to TKA rates.Results At all time points, patients who underwent UKA were associated with lower rates of infection compared with those who underwent HTOs (all OR ≤ 0.51, all p ≤ 0.010). After 1 year, patients who received UKAs were found to have lower risk of requiring a conversion to a TKA versus those who received HTOs (all OR ≤ 0.55, all p < 0.001). Complications such as dislocations, periprosthetic fractures, and surgical site infections were found at lower odds in UKA compared with HTO patients.Conclusion This study provides large-scale analyses demonstrating that UKA is associated with lower infection rates and fewer conversions to TKA compared with patients who have undergone HTO. Dislocations, periprosthetic fractures, and surgical site infections were also found to be lower among UKA patients. However, with careful patient selection, good results and preservation of the native knee are achieved with HTOs. Therefore, UKA versus HTO may be an important discussion to have with patients in an effort to lower the incidence of postoperative infections and complications.
Keywords: unicompartmental knee arthroplasty; infection; conversion; complication; high tibial osteotomy